TERANSFORMASI KEPEMIMPINAN KEPALA SEKOLAH DAN IMPLEMENTASI DALAM PENCEGAHAN PERUNDUNGAN DI SEKOLAH PADA PENDIDIKAN DASAR HINGGA MENENGAH: SISTEM LITERATUR RIVEW - Oktaviana Nirmala Purba; Putu Kerti Nitiasih; Putu Nanci Riastini; Ni Nyoman Trisna Herawati (Smart Education, 2026)
Abstract: Bullying behavior that occurs from elementary school to middle school is not only related to student behavior but also to the school's ability to implement prevention programs effectively and consistently. However, the literature discussing the relationship between transformational school leadership, school implementation capacity, and bullying prevention is still scattered across various concepts such as school climate, collective efficacy, teacher practices, principal responses, and whole-school approaches. This article aims to synthesize research on how transformational school leadership is positioned in relation to school implementation capacity for bullying prevention. A bibliometric-assisted systematic literature review was conducted using the Context, Intervention or Interest, Mechanism, and Outcome framework. The search was conducted in Scopus for publications from 2020 to 2026. The initial process identified 19 English-language records, retained 18 final journal articles after database screening, and used 10 key articles in the extraction matrix for narrative-integrative thematic synthesis. The review results show that school leadership is rarely portrayed as transformational leadership. Leadership emerges in the form of the principal's support, response to encountered problems, school vision, institutional leadership, and the principal's efforts in supporting the school's welfare. The capacity for school implementation emerges as a multidimensional construct involving the school climate, collective efficacy, teacher collaboration, shared practices, policy enforcement, reporting routines, and overall school coordination. This review concludes that bullying prevention should be understood as a process of school organizational capacity as a direct causal result of leadership. This study contributes to the examination of school principal leadership by clarifying how leadership-related conditions support anti-bullying practices at the school level. Keywords: bullying prevention, school principal leadership, school implementation capacity, systematic literature review, primary and secondary education. Abstrak: Perilaku perundungan yang terjadi mulai dari SD dan Sekolah menengah, tidak hanya berkaitan dengan perilaku siswa, tetapi berkaitan dengan kemampuan sekolah dalam menjalankan program pencegahan secara tepat sasaran dan konsisten. Namun, literatur yang membahas hubungan kepemimpinan kepala sekolah transformasional, kapasitas implementasi sekolah, dan pencegahan perundungan masih tersebar di berbagai konsep seperti, iklim sekolah, efikasi kolektif, praktik guru, respons kepala sekolah, dan pendekatan seluruh sekolah. Artikel ini bertujuan untuk mensintesis penelitian tentang bagaimana kepemimpinan kepala sekolah transformasional diposisikan dalam kaitannya dengan kapasitas implementasi sekolah untuk pencegahan perundungan. Tinjauan literatur sistematis yang dibantu bibliometrik dilakukan menggunakan kerangka kerja Konteks, Intervensi atau Minat, Mekanisme, dan Hasil. Pencarian dilakukan di Scopus untuk publikasi dari tahun 2020 hingga 2026. Proses awal mengidentifikasi 19 catatan berbahasa Inggris, mempertahankan 18 artikel jurnal akhir setelah penyaringan basis data, dan menggunakan 10 artikel utama dalam matriks ekstraksi untuk sintesis tematik naratif-integratif. Hasil tinjauan menunjukkan bahwa kepemimpinan kepala sekola jarang diorasikan sebagai kepemimpinan transformasional. Kepemimpinan muncul dalam bentuk dukungan kepala sekolah, respon terhadap masalah dihadapi, visi sekolah, kepemimpinan kelembagaan dan Upaya kepala sekolah dalam mendukung kesejahteraan sekolah. Kapasitas implementasi sekolah muncul sebagai konstruksi multidimensi yang melibatkan iklim sekolah, efikasi kolektif, kolaborasi guru, praktik bersama, pemberlakuan kebijakan, rutinitas pelaporan, dan koordinasi seluruh sekolah. Tinjauan ini menyimpulkan bahwa pencegahan perundungan harus dipahami sebagai proses kapasitas organisasi sekolah sebagai hasil kausal langsung dari kepemimpinan. Studi ini berkontribusi pada kajian kepemimpinan kepala sekolah dengan mengklarifikasi bagaimana kondisi terkait kepemimpinan mendukung praktik anti-perundungan di tingkat sekolah. Kata kunci: pencegahan perundungan, kepemimpinan kepala sekolah, kapasitas implementasi sekolah, tinjauan literatur sistematis, pendidikan dasar dan menengah.